2017
DOI: 10.1080/01616412.2017.1376457
|View full text |Cite
|
Sign up to set email alerts
|

Edaravone attenuates oxidative stress induced by chronic cerebral hypoperfusion injury: role of ERK/Nrf2/HO-1 signaling pathway

Abstract: Objectives The potential protective effects and mechanisms of edaravone have not been well elucidated in vascular dementia (VaD) induced by chronic cerebral hypoperfusion (CCH). The aim of this study was to investigate whether edaravone could improve cognitive damage in rats induced by CCH, and whether the effects of edaravone were associated with ERK/Nrf2/HO-1 signaling pathway. Methods CCH was induced by bilateral common carotid arteries occlusion (BCCAO). Sprague-Dawley (SD) rats were randomly divided into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(31 citation statements)
references
References 40 publications
2
29
0
Order By: Relevance
“…The results of oxidative stress and antioxidative enzymes in the present study indicated that Eda may alleviate the severity of asthma by suppressing oxidative injury and restoring the antioxidative enzyme, SOD. It has been shown that Eda may exert a protective effect through the Nrf2/HO-1 pathway (28)(29)(30). Li et al (57) revealed that Eda protects against hyperosmolarity-induced oxidative stress and apoptosis in primary human corneal epithelial cells by increasing the expression of Nrf2 and its target genes, such as HO-1 and GPx-1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of oxidative stress and antioxidative enzymes in the present study indicated that Eda may alleviate the severity of asthma by suppressing oxidative injury and restoring the antioxidative enzyme, SOD. It has been shown that Eda may exert a protective effect through the Nrf2/HO-1 pathway (28)(29)(30). Li et al (57) revealed that Eda protects against hyperosmolarity-induced oxidative stress and apoptosis in primary human corneal epithelial cells by increasing the expression of Nrf2 and its target genes, such as HO-1 and GPx-1.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al (28) revealed that Eda reduced iron-mediated hydrocephalus and behavioral disorders in rats through Nrf2/HO-1 activation. In an animal model of cognitive damage induced by chronic cerebral hypoperfusion (CCH), Eda reduced CCH-induced cognitive damage and increased SOD activity and HO-1 levels, but decreased MDA levels in the hippocampus through activation of the Nrf2 pathway (29). Liu et al (30) found that Eda increased neuronal density and decreased neuronal damage induced by kainite, which was administrated in the right hippocampus CA3 region using the sereotactic technique and this enhanced the expression of Nrf2 and HO-1.…”
Section: Edaravone Attenuates Experimental Asthma In Mice Through Indmentioning
confidence: 99%
“…Stroke is defined by sudden interruption of the local blood supply and by initiation of an anoxic and hypoglycemic state in the affected brain tissue. Under this condition, neuronal depolarization leads to the release of the neurotransmitter glutamate, which is the activator of the ionotropic NMDA receptor, resulting in Ca 2+ overload and excessive ROS production by mitochondria [ 98 , 99 , 100 , 101 , 102 ]. Furthermore, degradation of structural proteins of the vascular wall and loss of brain–blood barrier (BBB) integrity further enhance tissue oxygenation, which exacerbates ROS production.…”
Section: Nrf2 Mitochondrial Dynamics and Mitophagy In Neurologicmentioning
confidence: 99%
“…Furthermore, degradation of structural proteins of the vascular wall and loss of brain–blood barrier (BBB) integrity further enhance tissue oxygenation, which exacerbates ROS production. Although there are few studies on the alterations of the Nrf2 system in human patient specimens, Nrf2 pathway activators up-regulate the expression of tight junctional proteins (TJ) and promote redox metabolic functions and ATP synthesis with mitochondrial biogenesis, which protect neurons from stroke in animal models [ 98 , 99 , 100 , 101 , 102 , 103 , 104 ].…”
Section: Nrf2 Mitochondrial Dynamics and Mitophagy In Neurologicmentioning
confidence: 99%
“…Currently, the underlying mechanisms of VD have been linked to hippocampus neuron damage, inflammatory response, and oxidative stress ( Jiwa et al, 2010 ; Zhang et al, 2018 ). Furthermore, BCCAO-induced cognitive impairment and the occurrence of VD-like pathogenesis characterized by the deposition of beta-amyloid (Aβ) in the hippocampus are found ( Cai et al, 2017 ), and emerging strategies for interfering with the metabolism of Aβ might be promising therapeutic approaches to attenuate or reverse negative neurological consequences of BCCAO ( Won et al, 2013 ; Zhu et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%